The burden and trend prediction of atrial fibrillation and flutter associated with lead exposure: insights from the global burden of disease study 2021 - Lili Deng; Qinhong Li; Hongyan Li; Bin Li; Zugen Cheng; Ying Xiao (Frontiers in Cardiovascular Medicine)
BackgroundAtrial fibrillation and flutter (AF/AFL) are increasingly recognized as major contributors to global cardiovascular morbidity and mortality. Emerging evidence implicates environmental lead exposure as a modifiable risk factor for AF/AFL, yet the global burden and trends of AF/AFL attributable to lead exposure remain poorly characterized.MethodsWe used data from the Global Burden of Disease Study 2021 to estimate mortality, disability-adjusted life years (DALYs), and temporal trends in AF/AFL attributable to lead exposure from 1990 to 2021, with projections to 2030. Analyses were stratified by age, sex, and Socio-demographic Index (SDI) quintiles. Population-attributable fractions were calculated using comparative risk assessment methodology. Trend analyses utilized Joinpoint regression, and projections applied BAPC models.FindingsBetween 1990 and 2021, the global burden of AF/AFL attributable to lead exposure increased substantially. The number of lead-attributable AF/AFL deaths rose by 264.9%, and DALYs increased by 179.3%. Age-standardized rates for mortality and DALYs rose by 30.7% and 16.3%, respectively. The highest attributable burden occurred in older adults (≥60 years) and low-SDI regions, where lead exposure remains pervasive. Males consistently exhibited higher AF/AFL mortality and DALY rates than females, although the sex gap is narrowing. A significant negative correlation was observed between SDI and both mortality (r = –0.53, p < 0.001) and DALY rates (r = –0.53, p < 0.001) for lead-attributable AF/AFL. Projections indicate a continued rise in global AF/AFL burden linked to lead exposure in the absence of further mitigation efforts.InterpretationLead exposure is an important, preventable contributor to the rising global burden of AF/AFL, particularly among older adults and populations in low-SDI regions. Mechanistically, lead may increase AF/AFL risk through both direct myocardial effects and the amplification of established cardiovascular risk factors, notably hypertension. Our findings support urgent global policy action to reduce environmental lead exposure as an integral strategy for cardiovascular and arrhythmia prevention.